Appropriate Reassessment : Events and Memory in the European Parliament 1995-2025 - Mollberger,Jens (2025)
Historic events in motions for resolutions tabled by the parliament’s party groups between 1995-2025. While recent research trends within memory studies - under the influence of sociology - have tended to focus on agency, this thesis targets the content of memory politics by using historical research to confront political memories with their historical contexts. The thesis targets motions for resolutions related to historic memory produced by the Parliament’s party groups as its primary material, as motions appear to have been an hereto understudied category of material. While motions have featured as complementary evidence in previous research, no study which proposes to compare how the past is expressed in motions for resolutions has been identified. This thesis subjects them to systematic comparative analysis in order to explore how memories of the past interacted and changed across the party groups. The thesis has chosen to study memory by targeting the actualisation of events following renewed scholarly interest in the historical event as a concept within the research perspective of mnemohistory. The purpose of the thesis is to examine synchronic and diachronic patterns in what events were actualised, how they were actualised and what events remained non-used in the motions. The analysis of the material resulted in the erection of a typology which suggested to categorise the actualised events into main events, auxiliary events and partisan events. Following the erection of this typology, the analysis was structured in order to follow the actualisation of two main events - the Holocaust and the Holodomor - as well as the constellations of events within which these events appeared. Across the period of examination, a shift from universalist to particularist mnemonic articulations could be detected. In the motions which were tabled after the eastern enlargement of the European Union in 2004, a tendency to accentuate events from Eastern and Central Europe was observed. The tendency became observable in the motions of Conservative and Nationalist-Eurosceptic party groups, but emanated to a broader range of groups during the period of examination. Right leaning groups were also found to actualise past events to a higher degree, while Liberal, Green and Social Democratic groups oriented their motions towards the present rather than the past. Due to the rising anti-communist presumptions of European memory politics, the Communist party group, EUL/NGL, abstained from tabling motions during most of the examined procedures, causing their historic accounts to be invisible to the analysis. The Liberal formations exhibited the clearest shift in their articulation of the past, moving from a narrative revolving a positive account of the effects of European integration, to embracing dystopian visions of the past which dominated the mnemonic dynamic of the right-leaning groups across the period. Finally, the logic governing the actualisation of the past in the material turned from using history as a resource for integration to using it for symbolic intervention into the Russo-Ukrainian war.
Keywords: Memory studies; Historical Politics; Memory Politics; History; Contemporary History; European studies; Holocaust; Holodomor